Method of making functional particles for electrochemical cells and electrochemical cells comprising the same

CN115693029BActive Publication Date: 2026-10-27GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210585009.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-30
Filing Date
2022-05-26
Publication Date
2026-10-27
Estimated Expiration
2042-05-26

Smart Images

  • Figure CN115693029B_ABST
    Figure CN115693029B_ABST
Patent Text Reader

Abstract

Methods of making functional particles for electrochemical cells, such as functional lithium ion-exchanged zeolite particles and functional electrode particles, and electrochemical cells including the same are provided. One method includes combining a solution including (NH4)3PO4 with lithium ion-exchanged zeolite particles to form a first mixture. The method further includes adding a polymeric binder and a lithium salt to the first mixture to form a first slurry including functional lithium ion-exchanged zeolite particles including Li3PO4.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] introduction This section provides background information relating to this disclosure, which is not necessarily prior art.

[0002] Electrochemical batteries, such as battery packs, are devices that convert chemical energy into electrical energy through electrochemical reduction-oxidation (redox) reactions. In secondary or rechargeable battery packs, these electrochemical reactions are reversible, which allows the battery pack to undergo multiple charge and discharge cycles.

[0003] High-energy-density electrochemical batteries, such as lithium-ion battery packs, are used in a variety of consumer products and vehicles, such as hybrid electric vehicles (HEVs) and electric vehicles (EVs). Typical lithium-ion, lithium-sulfur, and lithium-metal battery packs include a first electrode, a second electrode, an electrolyte material, and a separator. One electrode acts as the positive or cathode, and the other as the negative or anode. A stack of battery cells can be electrically connected to increase the total output. Conventional rechargeable lithium-ion battery packs operate by reversibly transferring lithium ions back and forth between the negative and positive electrodes. A separator and electrolyte are placed between the negative and positive electrodes. The electrolyte is suitable for conducting lithium ions and can be in solid (e.g., solid-state diffusion) or liquid form. The negative and positive electrodes are typically carried on or connected to a metal current collector, for example, in the form of a thin layer of electrode material. The current collectors can be interconnected via a breakable external circuit, through which electrons can be transferred from one electrode to another during charging and discharging of the battery pack, while lithium ions move in the reverse direction through the electrochemical cell.

[0004] Lithium-ion battery packs can reversibly supply power to relevant load devices as needed. More specifically, the lithium-ion battery pack can supply power to the load device until the lithium content of the negative electrode is effectively depleted. The battery pack can then be recharged by reversing the flow of a suitable direct current between the electrodes.

[0005] During discharge, the negative electrode may contain a relatively high concentration of intercalated lithium, which is oxidized into lithium ions and electrons. Lithium ions are transported from the negative electrode (anode) to the positive electrode (cathode), for example, through the ion-conducting electrolyte solution contained within the pores of the intermediate porous membrane. Simultaneously, electrons are transported from the negative electrode to the positive electrode via an external circuit. Lithium ions can be assimilated into the positive electrode material through an electrochemical reduction reaction. After partial or complete discharge at its usable capacity, the battery pack can be recharged by an external power source, which reverses the electrochemical reactions that occurred during discharge.

[0006] During recharging, the lithium intercalated in the positive electrode is oxidized into lithium ions and electrons. Lithium ions are transported from the positive electrode to the negative electrode via the electrolyte through the porous membrane, while electrons are transported to the negative electrode via the external circuit. At the negative electrode, lithium cations are reduced to elemental lithium and stored in the negative electrode material for reuse.

[0007] During battery operation, trace amounts of water, hydrogen ions, hydrofluoric acid (HF), and dissociated transition metal ions (such as Mn) can be formed in the liquid electrolyte. 2+ and Fe 2+ / 3+ Lithium ions, polysulfides, and other target compounds adversely affect battery pack operation. Removing these target compounds from the liquid electrolyte during battery pack operation helps prevent or mitigate degradation of various battery pack components, thereby improving battery pack life and cycle performance. Therefore, there is a need for materials, such as functional particles, for electrochemical batteries that can remove these target compounds from the liquid electrolyte without inhibiting lithium ion transport or net flow through the liquid electrolyte, as well as methods for manufacturing these materials.

[0008] Overview This section provides a general overview of this disclosure and is not a full disclosure of its complete scope or all its features.

[0009] This application relates to the following: [1]. A method for preparing functional lithium-exchange zeolite particles for electrochemical batteries, the method comprising: (a) Combining a solution containing (NH4)3PO4 with lithium-ion exchange zeolite particles to form a first mixture; and (b) Adding a polymer binder and a lithium salt to a first mixture to form a first slurry containing functional lithium-ion exchange zeolite particles containing Li3PO4.

[0010] [2]. The method described in [1] above, wherein the functional lithium-ion exchange zeolite particles comprise cages defined by 8-membered rings, 9-membered rings, 10-membered rings, 12-membered rings or combinations thereof, and wherein the cages contain Li3PO4.

[0011] [3]. As described in [1] above, the functional lithium-ion exchange zeolite particles comprise zeolite materials having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA and combinations thereof.

[0012] [4]. As described in [1] above, the functional lithium-ion exchange zeolite particles comprise zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5 and combinations thereof.

[0013] [5]. The method described in [1] above, wherein the lithium salt is selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate and combinations thereof.

[0014] [6]. The method described in [1] above, wherein the concentrations of (NH4)3PO4 and lithium salt are each from about 0.01 M to about 1 M.

[0015] [7]. The method described in [1] above further includes one or more of the following: (c1) Applying a first slurry to a first side, a second side, or both sides of a porous membrane, and curing the first slurry to form a coating comprising functional lithium-ion exchange zeolite particles, wherein the coating is present on the first side, the second side, or both sides of the porous membrane; and (c2) The first slurry is combined with the porous membrane and the first slurry is cured to form a filler containing functional lithium-ion exchange zeolite particles within the porous membrane.

[0016] [8]. A method for preparing functional electrode particles for electrochemical batteries, the method comprising: (a) Combining a solution containing (NH4)3PO4 with a polymer binder to form a second mixture; (b) Add the electroactive particles to the second mixture; and (c) Adding a lithium salt to a second mixture to form a second slurry containing functional electrode particles, wherein the functional electrode particles comprise electroactive particles and Li3PO4.

[0017] [9]. The method described in [8] above, wherein the lithium salt is selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate and combinations thereof.

[0018]

[10] . The method described above [8], wherein the concentrations of (NH4)3PO4 and lithium salt are each from about 0.01 M to about 1 M.

[0019]

[11] . The method described above [8], wherein the electroactive particles comprise Li (1+x) Mn₂O₄, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M yO2, where 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0≤ P ≤ 1, x + y + z +p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, or a combination thereof.

[0020]

[12] . The method as described in the above [8], further comprising: (d) applying the second slurry to the third surface of the current collector; and (e) curing the second slurry to form an electrode layer comprising functional electrode particles.

[0021]

[13] . An electrochemical cell, comprising: a positive electrode layer comprising a first electroactive material; a negative electrode layer spaced apart from the positive electrode, wherein the negative electrode comprises a second electroactive material; a porous separator disposed between the opposing surfaces of the negative electrode layer and the positive electrode layer; a liquid electrolyte permeating one or more of the negative electrode layer, the positive electrode layer and the porous separator layer; and one or more of the following: (i) functional lithium ion exchange zeolite particles comprising Li3PO4; and (ii) functional electrode particles comprising (a) Li3PO4 and the first electroactive material, and / or (b) Li3PO4 and the second electroactive material.

[0022]

[14] . The electrochemical cell as described in the above

[13] , wherein when present, the functional lithium ion-exchanged zeolite particles are present as one or more of the following: (i) a coating present on the first side, the second side, or both the first and second sides of the porous separator; and (ii) a filler in the porous separator.

[0023]

[15] . The electrochemical cell as described in the above

[13] , wherein the functional lithium ion-exchanged zeolite particles comprise cages defined by 8-membered rings, 9-membered rings, 10-membered rings, 12-membered rings, or combinations thereof, and wherein the cages contain Li₃PO₄.

[0024]

[16] . The electrochemical cell as described in the above

[13] , wherein the functional lithium ion-exchanged zeolite particles comprise a zeolitic material having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof.

[0025]

[17] . The electrochemical cell as described in the above

[13] , wherein the functional lithium ion-exchanged zeolite particles comprise a zeolitic material selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

[0026]

[18] . The electrochemical cell as described in the above

[13] , wherein when present, the functional electrode particles are present in one or more of the following: (i) a positive electrode layer; and (ii) a second electrode layer.

[0027]

[19] . The electrochemical cell as described in the above

[13] , wherein the first electroactive material is selected from Li (1+x) Mn₂O₄, wherein 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O₄, wherein 0 ≤ x ≤ 0.5; LiCoO₂; Li(Ni x Mn y Co z )O₂, wherein 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O₂, wherein 0<x<0.2, y<0.2, and M is Al, Mg, or Ti; LiFePO₄, LiMn 2-x Fe xPO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ p ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur and combinations thereof.

[0028]

[20] . The electrochemical battery as described above

[13] , wherein the second electroactive material comprises lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, or combinations thereof.

[0029] This disclosure relates to a method for preparing functional lithium-ion exchange zeolite particles for use in electrochemical batteries. The method includes (a) combining a solution comprising (NH4)3PO4 with lithium-ion exchange zeolite particles to form a first mixture, and adding a polymer binder and a lithium salt to the first mixture to form a first slurry comprising functional lithium-ion exchange zeolite particles containing Li3PO4.

[0030] The functional lithium-ion exchange zeolite particles comprise cages defined by 8-membered, 9-membered, 10-membered, 12-membered rings, or combinations thereof, wherein the cages contain Li3PO4. For example, the functional lithium-ion exchange zeolite particles may include zeolite materials having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof, such as zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

[0031] The lithium salt can be selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, and combinations thereof.

[0032] The concentrations of (NH4)3PO4 and lithium salt can range from approximately 0.01 M to approximately 1 M.

[0033] The method may further comprise applying the first slurry to the first side of the porous separator, the second side of the porous separator, or both the first and second sides of the porous separator, and curing the first slurry to form a coating comprising functional lithium ion exchange zeolite particles. The coating may be present on the first side of the porous separator, the second side of the porous separator, or both the first and second sides of the porous separator. Additionally or alternatively, the method may further comprise combining the first slurry with the porous separator, and curing the first slurry to form a filler comprising functional lithium ion exchange zeolite particles within the porous separator.

[0034] In still further aspects, the present disclosure relates to a method of preparing functional electrode particles for an electrochemical cell. The method comprises (a) combining a solution comprising (NH4)3PO4 with a polymer binder to form a second mixture, (b) adding electroactive particles to the second mixture, and (c) adding a lithium salt to the second mixture to form a second slurry comprising functional electrode particles, wherein the functional electrode particles comprise electroactive particles and Li3PO4.

[0035] The lithium salt may be selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, and combinations thereof.

[0036] The concentration of each of (NH4)3PO4 and the lithium salt may be from about 0.01 M to about 1 M.

[0037] The electroactive particles may comprise Li (1+x) Mn2O4, wherein 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, wherein 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, wherein 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, wherein 0 < x < 0.2, y < 0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, wherein 0 < x < 0.3; LiNiCoAlO2; LiMPO4, wherein M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p)O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z +p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate or combinations thereof.

[0038] The method may further include applying a second slurry to a third surface of the current collector and curing the second slurry to form an electrode layer containing functional electrode particles.

[0039] In some aspects, this disclosure relates to an electrochemical battery. The electrochemical battery includes a positive electrode layer comprising a first electroactive material and a negative electrode layer spaced apart from the positive electrode. The negative electrode comprises a second electroactive material. The electrochemical battery further includes a porous membrane disposed between opposing surfaces of the negative and positive electrodes and a liquid electrolyte permeating one or more of the negative electrode layer, the positive electrode layer, and the porous membrane. The electrochemical battery further includes one or more of the following: (i) functional lithium-ion exchange zeolite particles comprising Li3PO4; and (ii) functional electrode particles comprising (a) Li3PO4 and the first electroactive material, and / or (b) Li3PO4 and the second electroactive material. When present, the functional lithium-ion exchange zeolite particles may be present as one or more of the following: (i) a coating present on a first side, a second side, or both sides of the porous membrane; and (ii) a filler in the porous membrane. When present, the functional electrode particles may be present in one or more of the following: (i) the positive electrode layer; and (ii) the second electrode layer.

[0040] The functional lithium-ion exchange zeolite particles comprise cages defined by 8-membered, 9-membered, 10-membered, 12-membered rings, or combinations thereof, wherein the cages contain Li3PO4. For example, the functional lithium-ion exchange zeolite particles may include zeolite materials having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof, such as zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

[0041] The first electroactive material can be selected from Li.(1+x) Mn₂O₄, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O₄, where 0 ≤ x ≤ 0.5; LiCoO₂; Li(Ni x Mn y Co z )O₂, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O₂, where 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO₄, LiMn 2-x Fe x PO₄, where 0 < x < 0.3; LiNiCoAlO₂; LiMPO₄, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O₂, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ p ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO₂; Li₂Fe x M 1-x PO₄, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn₂O₄; LiFeSiO₄; LiNi 0.6 Mn 0.2 Co 0.2 O₂ (NMC622), LiMnO₂ (LMO), activated carbon, sulfur and combinations thereof.

[0042] The second electroactive material may include lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate or a combination thereof.

[0043] Other applicable fields will become apparent from the description provided herein. The descriptions and specific examples in this overview are intended for illustrative purposes only and are not intended to limit the scope of the present disclosure. Brief Description of the Drawings The drawings described herein are for illustrative purposes only of selected embodiments and not all possible embodiments, and are not intended to limit the scope of the present disclosure.

[0044] Figure 1A is a flowchart of an exemplary method for preparing functional lithium ion-exchanged zeolite particles according to the present disclosure; Figure 1B This is a diagram illustrating an exemplary functional lithium-ion exchange zeolite particle according to the present disclosure; Figure 1C This is an illustration of a porous membrane including the coating according to the present disclosure; Figure 1D This is a flowchart of another exemplary method for preparing functional lithium-ion exchange zeolite particles according to this disclosure; Figure 2A This is a flowchart of an exemplary method for preparing functional electrode particles according to the present disclosure; Figure 2B This is a diagram of an electrode layer including functional electrode particles according to the present disclosure; Figure 3 This is a schematic diagram of an exemplary electrochemical battery pack according to the present disclosure; Figure 4 This is a schematic diagram of another exemplary electrochemical battery pack according to this disclosure; Figure 5 This is an X-ray diffraction (XRD) pattern of Li3PO4 particles formed according to Example 1. Figure 6A and 6B This is a scanning electron microscope (SEM) image of Li3PO4 particles formed according to Example 1.

[0045] In the various views of the accompanying drawings, the corresponding reference numerals refer to the corresponding components.

[0046] Detailed Explanation Exemplary embodiments are provided to make this disclosure thorough and to fully communicate its scope to those skilled in the art. Numerous specific details, such as examples of specific compositions, components, apparatuses, and methods, are set forth to provide a full understanding of embodiments of this disclosure. It will be apparent to those skilled in the art that the specific details are not required, that exemplary embodiments may be embodied in many different forms, and that none of them should be construed as limiting the scope of this disclosure. In some exemplary embodiments, well-known methods, well-known apparatus structures, and well-known technologies are not described in detail.

[0047] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms “a” and “the” used herein are intended to include the plural forms as well. The terms “comprising,” “including,” and “having” are inclusive and thus specify the presence of a designated element, component, composition, step, integer, operation, and / or component, but do not exclude the presence or inclusion of one or more other elements, integers, steps, operations, components, and / or combinations thereof. Although the open-ended term “comprising” should be understood as a non-limiting term used to describe and claim protection for the various embodiments described herein, in some respects, the term may be understood as a more restrictive and binding term, such as “consisting of” or “substantially consisting of.” Therefore, for any given embodiment in which compositions, materials, components, elements, components, integers, operations, and / or process steps are listed, this disclosure also expressly includes embodiments consisting of or substantially consisting of these listed compositions, materials, components, components, components, components, integers, operations, and / or process steps. In the case of “consisting of…”, the alternative embodiment does not include any additional compositions, materials, components, elements, elements, integers, operations and / or process steps, while in the case of “essentially composed of…”, such an embodiment does not include any additional compositions, materials, components, elements, elements, integers, operations and / or process steps that materially affect the essential and novel features, but may include any compositions, materials, components, elements, elements, integers, operations and / or process steps that do not materially affect the essential and novel features.

[0048] Any method steps, processes, and operations described herein should not be construed as necessarily requiring them to be performed in the particular order discussed or illustrated, unless expressly specified as such. It should also be understood that additional or alternative steps may be used unless otherwise indicated.

[0049] When a component, element, or layer is mentioned as being “on,” “joined,” “connected,” or “coupled” to another component or layer, it may be directly on, joined, connected, or coupled to the other component, element, or layer, or there may be intermediate elements or layers. Conversely, when an element is mentioned as being “directly on,” “directly joined,” “directly connected,” or “directly coupled” to another component or layer, there are no intermediate elements or layers. Other terms used to describe relationships between elements should be interpreted in a similar manner (e.g., “between” vs. “directly between,” “adjacent” vs. “directly adjacent,” etc.). The term “and / or” as used herein includes any and all combinations of one or more of the related listed items.

[0050] Although the terms first, second, third, etc., may be used herein to describe various steps, elements, components, regions, layers, and / or sections, these steps, elements, components, regions, layers, and / or sections should not be limited by these terms unless otherwise specified. These terms are used only to distinguish one step, element, component, region, layer, or section from another. Unless the context clearly indicates otherwise, terms such as “first,” “second,” and other ordinal terms used herein do not imply order or sequence. Therefore, the first step, element, component, region, layer, or section discussed below may be referred to as the second step, element, component, region, layer, or section without departing from the teachings of the exemplary embodiments.

[0051] For ease of description, spatially or temporally relative terms such as “front,” “back,” “inner,” “outer,” “lower,” “below,” “lower part,” “upper part,” “upper part,” etc., may be used herein to describe the relationship between one element or component and another element or component as shown in the accompanying drawings. Spatially or temporally relative terms are intended to encompass different orientations of the device or system in use or operation other than those depicted in the accompanying drawings.

[0052] Throughout this disclosure, numerical values ​​represent approximate measurements or range limits to include slight deviations from a given value and embodiments that substantially have the listed values ​​as well as embodiments that precisely have the listed values. Except in the detailed embodiments provided at the end, all numerical values ​​of parameters (e.g., quantities or conditions) in this specification (including the appended claims) should be understood to be modified in all cases by the term “about,” regardless of whether “about” actually precedes the numerical value. “About” means that the specified numerical value allows for a certain degree of slight imprecision (closeness to the value; approximate or reasonably close to the value; almost). If the imprecision provided by “about” is not understood in this common sense in the art, “about” as used herein refers at least to variations that may arise from common methods of measuring and using such parameters. For example, “about” may include variations of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some respects, optionally less than or equal to 0.1%.

[0053] In addition, the disclosure of the range includes all values ​​across the entire range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.

[0054] Exemplary embodiments will now be described more fully with reference to the accompanying drawings.

[0055] I. Methods for preparing functional particles for electrochemical batteries This paper provides a method for preparing functional particles for electrochemical batteries. As used herein, "functional particles" refers to particles comprising one or more complexes, such as Li3PO4, Al2O3, and SiO2, which can be nanoscale and can act as hydrofluoric acid (HF) scavengers in electrochemical batteries. Furthermore, the inclusion of Li3PO4 in the particles is advantageous because Li3PO4 possesses flame-retardant properties and can help prevent ignition during thermal runaway events in the battery pack. The term "nanoscale" refers to particles with a diameter of 1 nm to 900 nm. Functional particles can be functional lithium-ion exchange zeolite particles and / or functional electrode particles. It has been found that such functional particles can be formed by mixing a first precursor, such as (NH4)3PO4, with a second precursor, such as a lithium salt, in a stepwise manner as further described below, so as to advantageously form Li3PO4 in situ to obtain a uniform distribution of Li3PO4 particles.

[0056] For example, this document provides a method for preparing functional lithium-ion exchanged zeolite particles. These functional lithium-ion exchanged zeolite particles may comprise or consist essentially of particles of one or more natural or synthetic zeolite materials. As used herein, “zeolite” is defined as a synthetic or natural crystalline material having a porous framework structure constructed of tetrahedral atoms (e.g., silicon, aluminum, phosphorus) connected by bridging oxygen atoms. Zeolites may comprise a three-dimensional framework of AlO2 and SiO2 tetrahedral units and extra-framework cations. Each AlO2 unit introduces a negative charge into the framework, which is counteracted by the extra-framework cations. The extra-framework cations may be organic or inorganic in nature. As used herein, the term “lithium-ion exchanged zeolite particle” refers to a zeolite that has undergone ion exchange with lithium ions so that multiple lithium ions exist within the zeolite as free ions and / or as extra-framework ions.

[0057] In various aspects, functional lithium-ion exchange zeolite particles can contain a three-dimensional framework of AlO2 and SiO2 tetrahedral units and an extra-framework lithium cation (Li). + The amount of extra-framework lithium cations present in functional lithium-ion exchange zeolite particles can be at least partially determined by the Si:Al ratio of a particular zeolite material and the cation exchange capacity (CEC) of that zeolite material. In functional lithium-ion exchange zeolite particles, lithium cations (Li... + The extra-skeletal cations that can constitute the zeolite particles may be greater than or equal to about 90 atomic percent (at.%), greater than or equal to about 95 at.%, greater than or equal to 99 at.%, or about 100 at.%. In some embodiments, the zeolite may be in a dehydrated form.

[0058] The zeolite framework has cage-like or channel-like voids or pores between tetrahedra, defined by rings of interconnected oxygen (O), silicon (Si), phosphorus (P), and / or aluminum (Al) atoms. Zeolite particles may have an average pore size of less than or equal to about 1.5 nm, less than or equal to about 1 nm, less than or equal to about 0.75 nm, less than or equal to about 0.5 nm, less than or equal to about 0.25 nm, less than or equal to about 0.1 nm, or about 0.05 nm. Additionally or alternatively, zeolite particles may have an average pore size greater than or equal to about 0.1 nm to less than or equal to about 1.5 nm, greater than or equal to about 0.1 nm to less than or equal to about 1 nm, or greater than or equal to about 0.35 nm to less than or equal to about 0.7 nm. Zeolite materials having pore openings with the width or diameter described above may include zeolite materials having pore openings defined by 8-membered, 9-membered, 10-membered, and / or 12-membered rings.

[0059] Examples of known zeolite frameworks are given in “Atlas of Zeolite Frameworks,” 6th revised edition, published under the name of the “Structure Commission of the International Zeolite Association,” Ch. Baerlocher, LBMcCusker, DH Olson, eds., Elsevier, New York (2007) and the corresponding website http: / / www.iza-structure.org / databases / . Under this definition, a zeolite can refer to a crystalline structure of aluminosilicates having a zeolite framework type, as well as oxides containing heteroatoms other than silicon and aluminum. Such heteroatoms can include any heteroatom generally known to be suitable for inclusion in a zeolite framework, such as gallium, boron, germanium, phosphorus, zinc, antimony, tin, and / or other transition metals that can substitute for silicon and / or aluminum in the zeolite framework.

[0060] In some embodiments, the functional lithium-ion exchange zeolite particles, for example before operation in an electrochemical cell, may contain less than or equal to about 10 at.%, less than or equal to about 5 at.%, less than or equal to about 1 at.%, less than or equal to about 0.5 at.%, or less than or equal to about 0.1 at.% of one or more of the following extra-skeletal cations: Na + K + Mg 2+ Ca + H + and NH4 +In some embodiments, the functional lithium-ion exchange zeolite particles may contain less than or equal to about 1 at.% or less than or equal to about 0.1 at% Na. + H + Ca + K + and / or NH4 + One or more of the following. In some embodiments, the lithium-ion exchange zeolite particles contain NH4+. + The amount may be more than one or more of the following cations: Na + K + Mg 2+ and Ca + Additionally or alternatively, lithium-ion exchange zeolite particles may substantially be free of one or more of the following: Na + K + Mg 2+ NH4 + and Ca + cation.

[0061] like Figure 1A As shown, the method may include step 105: for example, mixing a suitable amount of (NH4)3PO4 with water or solvent in a first container at a sufficient temperature for a sufficient amount of time to form a solution (aqueous or non-aqueous) containing (NH4)3PO4. In a further step 110, the method includes, for example, combining the solution containing (NH4)3PO4 with lithium-ion exchange zeolite particles in a first container at a sufficient temperature for a sufficient amount of time to form a first mixture. In any embodiment, the concentration of (NH4)3PO4 in step 105 and combined with the lithium-ion exchange zeolite particles in step 110 may be greater than or equal to about 0.001 M, greater than or equal to about 0.01 M, greater than or equal to about 0.05 M, greater than or equal to about 0.1 M, greater than or equal to about 0.25 M, greater than or equal to about 0.5 M, greater than or equal to about 0.75 M, greater than or equal to about 1 M, greater than or equal to about 1.5 M, greater than or equal to about 2 M, or about 5 M; or about 0.001 M to about 5 M, about 0.01 M to about 5 M, about 0.01 M to about 2 M, about 0.01 M to about 1.5 M, about 0.01 M to about 1 M, about 0.01 M to about 0.75 M, about 0.1 M to about 5 M, about 0.1 M to about 2 M, or about 0.1 M to about 1 M.

[0062] In step 115, the method includes adding a polymer binder and a lithium salt to a first mixture at a sufficient temperature for a sufficient amount of time to form a first slurry comprising functional lithium-ion exchange zeolite particles containing Li3PO4. It is understood herein that the polymer binder and lithium salt may be added to the first mixture substantially simultaneously (or in parallel), or that the polymer binder and lithium salt may be added to the first mixture sequentially at different times. For example, the polymer binder may be added to the first mixture followed by the lithium salt, or the lithium salt may be added to the first mixture followed by the polymer binder.

[0063] In any of steps 105, 110, and 115, mixing may be performed. Additionally or alternatively, each of steps 105, 110, and 115 may be performed at a temperature greater than or equal to about 18°C, greater than or equal to about 20°C, greater than or equal to about 25°C, greater than or equal to about 30°C, greater than or equal to about 60°C, greater than or equal to about 80°C, greater than or equal to about 90°C, greater than or equal to about 100°C, greater than or equal to about 120°C, or about 150°C; approximately 18°C ​​to about 150°C, approximately 18°C ​​to about 120°C, approximately 18°C ​​to about 90°C, approximately 18°C ​​to about 60°C, approximately 25°C to about 120°C, approximately 50°C to about 90°C, or approximately 80°C to about 120°C. Additionally or alternatively, each of steps 105, 110, and 115 may be performed for approximately 1 minute, approximately 5 minutes, approximately 10 minutes, approximately 15 minutes, approximately 30 minutes, approximately 60 minutes, approximately 2 hours, approximately 6 hours, approximately 12 hours, approximately 18 hours, approximately 24 hours, or approximately 48 hours; or approximately 1 minute to approximately 48 hours, approximately 1 minute to approximately 24 hours, approximately 1 minute to approximately 12 hours, or approximately 1 minute to approximately 6 hours. Approximately 1 minute to approximately 2 hours, approximately 5 minutes to approximately 48 hours, approximately 5 minutes to approximately 24 hours, approximately 10 minutes to approximately 48 hours, approximately 10 minutes to approximately 24 hours, approximately 10 minutes to approximately 12 hours, approximately 10 minutes to approximately 6 hours, approximately 10 minutes to approximately 2 hours, approximately 30 minutes to approximately 48 hours, approximately 30 minutes to approximately 24 hours, approximately 60 minutes to approximately 48 hours, approximately 60 minutes to approximately 24 hours, approximately 6 hours to approximately 24 hours, approximately 12 hours to approximately 24 hours, approximately 18 hours to approximately 24 hours, or approximately 24 hours to approximately 48 hours. For example, steps 105 and / or 110 may be performed at a temperature of approximately 18°C ​​to approximately 90°C for approximately 1 minute to approximately 2 hours, and step 115 may be performed at a temperature of approximately 18°C ​​to approximately 60°C for approximately 10 minutes to approximately 2 hours.

[0064] The polymer binder and lithium salt may each be present in an aqueous or non-aqueous solution (i.e., in a solvent) before being added to the first mixture. The polymer binder may comprise any material containing or including a polymer and may comprise composite materials comprising a combination of polymeric and non-polymeric materials. The term “polymer” is used in its broad sense to refer to homopolymers and heteropolymers. Homopolymers are made from a single type of polymer, while heteropolymers (also called copolymers) are made from two (or more) different types of monomers. In one form, the polymer binder may be formed from a two-component polymer binder system comprising a polymer precursor component and a crosslinking component. In this case, the method may comprise the following general steps: (1) providing a polymer precursor component comprising a polymer or polymer precursor (e.g., monomer or oligomer) dissolved or uniformly dispersed in a solvent or water, (2) adding the polymer precursor component to the first mixture to form an intermediate mixture, and then (3) mixing the crosslinking component into the intermediate mixture to form a first slurry. The intermediate mixture may have a viscosity in the range of 400–1200 mPa∙s at a temperature of about 25°C. When the polymer precursor component and the crosslinking component are combined during the formation of the first slurry, a chemical reaction called polymerization occurs between the components to bind them together (e.g., by forming suitable covalent bonds) to form a crosslinked network called a polymer. The mass ratio of the polymer precursor component to the crosslinking component can range from about 10:1 to about 5:1. For example, the mass ratio of the polymer precursor component to the crosslinking component can be about 9:1.

[0065] Prior to the addition of the crosslinking components, additional solvents or water may be added to the polymer precursor components and / or intermediate mixtures to control or adjust the viscosity and / or thixotropic or rheological properties of the slurry. Some specific examples of suitable aqueous and non-aqueous solvents that may be included in or added to the polymer precursor components and / or intermediate mixtures include: water, N-methyl-2-pyrrolidone (NMP), toluene, and combinations thereof.

[0066] Some specific examples of suitable polymer precursor components include: alginates (e.g., sodium alginate and / or ammonium alginate), polyvinyl alcohol (PVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), fluorine-acrylic hybrid latex, and combinations thereof.

[0067] The crosslinking component may comprise polymeric or non-polymeric materials. For example, the crosslinking component may comprise polymers or polymer precursors (e.g., monomers or oligomers). Some specific examples of suitable crosslinking components include: dimethylol urea, melamine-formaldehyde resin, polyamide epichlorohydrin (PAE) resin, N-(1-hydroxy-2,2-dimethoxyethyl)acrylamide, N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, and combinations thereof.

[0068] In any embodiment, the lithium salt may comprise lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium chloride (LiCl), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), or a combination thereof. In one embodiment, the lithium salt may be LiOH. In any embodiment, the concentration of the lithium salt added in step 115 may be greater than or equal to about 0.001 M, greater than or equal to about 0.01 M, greater than or equal to about 0.05 M, greater than or equal to about 0.1 M, greater than or equal to about 0.25 M, greater than or equal to about 0.5 M, greater than or equal to about 0.75 M, greater than or equal to about 1 M, greater than or equal to about 1.5 M, greater than or equal to about 2 M, or about 5 M; or about 0.001 M to about 5 M, about 0.01 M to about 5 M, about 0.01 M to about 2 M, about 0.01 M to about 1.5 M, about 0.01 M to about 1 M, about 0.01 M to about 0.75 M, about 0.1 M to about 5 M, about 0.1 M to about 2 M, or about 0.1 M to about 1 M.

[0069] The addition of lithium salt to the first mixture can be represented by the following exemplary reaction equation (1): 3 LiOH + (NH4)3PO4 = Li3PO4 ↓ + 3NH3 ↑ + 3 H2O (1).

[0070] In any embodiment, the ratio of lithium salt to (NH4)3PO4 may be at least about 1% higher than the stoichiometric ratio of lithium salt to (NH4)3PO4, for example, greater than about 2%, greater than about 3%, greater than about 4%, greater than about 5%, greater than about 7%, or about 10% higher than the stoichiometric ratio of lithium salt to (NH4)3PO4. In other words, an excess of about 10% or less (e.g., 1%, 2%, 3%, 4%, 5%, etc.) of lithium salt may be used.

[0071] As described above, the first slurry comprises functional lithium-ion exchange zeolite particles containing Li3PO4 and a polymer binder. It has been found that the Li3PO4 formed during the reaction can exist within the cages of the functional lithium-ion exchange zeolite particles. For example, as... Figure 1BAs described herein, the functional lithium-ion exchange zeolite particles 100 formed according to the method described above may include Li + Cation 115 serves as an extra-framework cation. Additionally, functional lithium-ion exchange zeolite particles may also include Li3PO4 complex 126. For example... Figure 1B As shown, the Li3PO4 complex 126 may be present within or contained within the cage 112 of the functional lithium-ion exchange zeolite particle 100. In other words, the cage 112 may include or contain one or more Li3PO4 complexes 126.

[0072] In this paper, it is proposed that the concentrations of (NH4)3PO4 and lithium salts (e.g., LiOH) can be adjusted based on the amount of cations in the lithium-ion exchange zeolite particles to ensure the formation of Li3PO4 within the cage of the lithium-ion exchange zeolite particles.

[0073] The zeolite particles before being combined with (NH4)3PO4 and lithium salts to form functional lithium-ion exchange zeolite particles are referred to herein as "lithium-ion exchange zeolite particles". Lithium-ion exchange zeolite particles may have a framework selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof. For example, lithium-ion exchange zeolite particles may contain zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof. Furthermore, lithium-ion exchange zeolite particles and the functional lithium-ion exchange zeolite particles formed therefrom may have substantially the same pore size, substantially the same particle size, and substantially the same SiO2:Al2O3 ratio as described herein. For example, lithium-ion exchange ZSM-5 particles (lithium-ion exchange zeolite particles) with an average pore size of approximately 0.5 nm, an average particle size of 100 nm, and a SiO2:Al2O3 ratio of approximately 20 can be used to form functional lithium-ion exchange ZSM-5 particles with essentially the same pore size, particle size, and SiO2:Al2O3 ratio as the initial lithium-ion exchange ZSM-5 particles. In this paper, it is assumed that the resulting functional lithium-ion exchange zeolite particles may exhibit certain variations (e.g., approximately 1-5%) in pore size, particle size, and SiO2:Al2O3 ratio compared to the lithium-ion exchange zeolite particles.

[0074] In any embodiment, the functional lithium-ion exchange zeolite particles may have an average particle size of less than or equal to about 20 μm, less than or equal to about 15 μm, less than or equal to about 10 μm, less than or equal to about 5 μm, less than or equal to about 1 μm, less than or equal to about 100 nm, less than or equal to about 50 nm, or about 10 nm. Additionally or alternatively, the functional lithium-ion exchange zeolite particles may have an average particle size of greater than or equal to about 10 nm to less than or equal to about 20 μm, greater than or equal to about 10 nm to less than or equal to about 10 μm, greater than or equal to about 10 nm to less than or equal to about 5 μm, or greater than or equal to about 10 nm to less than or equal to about 1 μm.

[0075] Zeolite crystal structures comprise interstitial spaces (or cages) at the molecular size. Therefore, zeolites can be used as adsorbents to selectively adsorb molecules by retaining them within these interstitial spaces. Pathways into the interstitial spaces within the zeolite are provided by pore openings (or channels) in the zeolite lattice, defined by rings of interconnected oxygen (O), silicon (Si), and / or aluminum (Al) atoms. The size and shape of these pore openings limit the size and shape of the molecules that the zeolite can adsorb and depend at least in part on the number of tetrahedral units (or oxygen atoms) constituting the rings and the type of extra-framework cations present within the zeolite. Thus, functional lithium-exchange zeolite particles can have an average pore size capable of achieving one or more of the following: (i) selectively adsorbing water molecules (e.g., trace amounts) from liquid electrolytes without adsorbing organic solvent molecules or lithium salt ions from the electrolyte solution; and (ii) allowing essentially only Li-12 molecules to migrate while blocking polysulfide migration. +Ions pass through a membrane, for example, in a lithium-sulfur battery pack. In some embodiments, the functional lithium-ion exchange zeolite particles may have an average pore size greater than the ionic radius of water (H₂O) but smaller than the ionic radius of organic solvent molecules in the electrolyte solution. Specifically, the functional lithium-ion exchange zeolite particles may have an average pore size of less than or equal to about 1.5 nm, less than or equal to about 1 nm, less than or equal to about 0.75 nm, less than or equal to about 0.5 nm, less than or equal to about 0.25 nm, less than or equal to about 0.1 nm, or about 0.05 nm. Additionally or alternatively, the functional lithium-ion exchange zeolite particles may have an average pore size of greater than or equal to about 0.05 nm to less than or equal to about 1.5 nm, greater than or equal to about 0.05 nm to less than or equal to about 1 nm, greater than or equal to about 0.1 nm to less than or equal to about 1 nm, or greater than or equal to about 0.25 nm to less than or equal to about 0.75 nm. Zeolite materials having pore openings with the width or diameter described above may include zeolite materials having pore openings defined by 8-membered rings, 9-membered rings, 10-membered rings and / or 12-membered rings.

[0076] In some embodiments, the functional lithium-ion exchange zeolite particles may comprise particles of zeolite material having a SiO2:Al2O3 ratio of less than or equal to about 50, less than or equal to about 40, less than or equal to about 30, less than or equal to about 20, or about 10. The functional lithium-ion exchange zeolite particles may comprise particles of zeolite material having a SiO2:Al2O3 ratio in the range of greater than or equal to about 10 to less than or equal to about 50, greater than or equal to about 10 to less than or equal to about 40, greater than or equal to about 10 to less than or equal to about 20, greater than or equal to about 20 to less than or equal to about 50, about 20 to about 40, or about 30 to about 50. In some embodiments, functional lithium-ion exchange zeolite particles having more SiO2 than Al2O3, for example having a SiO2:Al2O3 ratio greater than about 10, are preferred, for example, for improved stability. In other embodiments, functional lithium-ion exchange zeolite particles with more Al2O3 than SiO2 are provided, for example, having a SiO2:Al2O3 ratio of less than about 10, for example, to improve the hydrofluoric acid (HF) removal function of the porous membrane to protect the positive electrode.

[0077] Functional lithium-ion exchange zeolite particles may contain zeolite materials with a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof. For example, functional lithium-ion exchange zeolite particles may contain zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

[0078] Additionally or alternatively, the method may further include optional step 120, which includes applying a first slurry to a substrate, such as a porous membrane, and curing the first slurry to form a coating comprising functional lithium-ion exchange zeolite particles. For example, as Figure 1C As described herein, a first slurry may be applied to a first side 50 and a second side of a porous membrane 26 and cured to form a coating 60 comprising functional lithium-ion exchange zeolite particles (e.g., functional lithium-ion exchange zeolite particles 100). It is understood herein that the first slurry may be applied to the first side 50 of the porous membrane 26, or to the second side 55 of the porous membrane 26, or to both the first and second sides 50, 55 of the porous membrane 26. Therefore, the coating 60 may be present on the first side 50 of the porous membrane 26, or on the second side 55 of the porous membrane 26, or on both the first and second sides 50, 55 of the porous membrane 26.

[0079] The first slurry may be applied by any suitable method or otherwise. For example, the slurry may be coated or cast onto the first and / or second sides 50, 55 of the diaphragm 26. The first slurry may then be cured by any suitable method to form a coating 60. Thus, the coating 60 comprises functional lithium-ion exchange zeolite particles, including Li3PO4, dispersed within a polymer binder. For example, the first slurry may be dried and cured (e.g., thermosetting, ultraviolet (UV) curing) to remove any solvents and / or water and to complete the crosslinking or polymerization reaction. Drying and / or curing may be achieved by heating the first slurry present on the diaphragm to a suitable temperature, for example, in the range of about 30°C to about 140°C, for about 3 minutes to about 2 hours. Additionally or alternatively, drying may be achieved by heating the first slurry present on the diaphragm to a suitable temperature and also exposing the first slurry present on the diaphragm to ultraviolet radiation. Subsequently, the diaphragm 26, including the first and / or second active layers 50, 55, may be held at room temperature and exposed to a negative pressure environment for 3 to 12 hours to remove residual volatile compounds (e.g., water). In some cases, a first slurry may be applied to the first or second side 50, 56 of the diaphragm 26 and cured, and then the first slurry may be applied to the opposite side 50, 56 of the diaphragm 26 and cured, after which the diaphragm 26 with coating 60 may be exposed to a negative pressure environment.

[0080] Additionally or alternatively, the method may further include, as Figure 1DOptional step 125, as shown, includes incorporating a first slurry with a porous membrane and curing the first slurry to form a filler containing functional lithium-ion exchange zeolite particles present within the porous membrane. For example, the first slurry may be mixed with a precursor material for forming the porous membrane (e.g., a polymer precursor, a nonwoven material described below, or a fibrous membrane) and cured during the fabrication of the porous membrane. Curing may be performed as described above, for example by drying and curing (e.g., thermal curing, ultraviolet (UV) curing) to remove any solvents and / or water and to complete the crosslinking or polymerization reaction.

[0081] In a further embodiment, a method for preparing functional electrode particles for electrochemical cells is provided. For example, such as... Figure 2A The method, as described herein, may include step 205: mixing a suitable amount of (NH4)3PO4 with water or a solvent in a first container at a sufficient temperature for a sufficient amount of time to form a solution (aqueous or non-aqueous) containing (NH4)3PO4. In a further step 210, the method includes combining the solution containing (NH4)3PO4 with a polymer binder as described herein, in a manner as described herein, for a sufficient amount of time, for example, in a first container at a sufficient temperature, to form a second mixture. The polymer binder may be present in the aqueous or non-aqueous solution (i.e., in a solvent) prior to being added to the aqueous solution containing (NH4)3PO4. In any embodiment, the concentration of (NH4)3PO4 in step 205 and incorporated with the polymer binder in step 210 may be greater than or equal to about 0.001 M, greater than or equal to about 0.01 M, greater than or equal to about 0.05 M, greater than or equal to about 0.1 M, greater than or equal to about 0.25 M, greater than or equal to about 0.5 M, greater than or equal to about 0.75 M, greater than or equal to about 1 M, greater than or equal to about 1.5 M, greater than or equal to about 2 M, or about 5 M; or about 0.001 M to about 5 M, about 0.01 M to about 5 M, about 0.01 M to about 2 M, about 0.01 M to about 1.5 M, about 0.01 M to about 1 M, about 0.01 M to about 0.75 M, about 0.1 M to about 5 M, about 0.1 M to about 2 M, or about 0.1 M to about 1 M.

[0082] The method may further include step 215 of adding electroactive particles to a second mixture and step 220 of adding a lithium salt (e.g., LiOH) as described herein to the second mixture to form a second slurry containing functional electrode particles. The functional electrode particles include electroactive particles and Li3PO4 particles or complexes. The addition of the lithium salt to the second mixture may also be represented by the above exemplary reaction equation (1) under excess conditions as described above. It is considered herein that the electroactive particles and the lithium salt may be added to the second mixture substantially simultaneously (or in parallel), or that the electroactive particles and the lithium salt may be added to the second mixture sequentially at different times. For example, the electroactive particles may be added to the second mixture followed by the lithium salt, or the lithium salt may be added to the second mixture followed by the electroactive particles. The lithium salt may be present in an aqueous solution or a non-aqueous solution (i.e., in a solvent) prior to being added to the second mixture. In any embodiment, the concentration of the lithium salt added in step 220 may be greater than or equal to about 0.001 M, greater than or equal to about 0.01 M, greater than or equal to about 0.05 M, greater than or equal to about 0.1 M, greater than or equal to about 0.25 M, greater than or equal to about 0.5 M, greater than or equal to about 0.75 M, greater than or equal to about 1 M, greater than or equal to about 1.5 M, greater than or equal to about 2 M, or about 5 M; or about 0.001 M to about 5 M, about 0.01 M to about 5 M, about 0.01 M to about 2 M, about 0.01 M to about 1.5 M, about 0.01 M to about 1 M, about 0.01 M to about 0.75 M, about 0.1 M to about 5 M, about 0.1 M to about 2 M, or about 0.1 M to about 1 M. In any embodiment, the ratio of lithium salt to (NH4)3PO4 may be at least about 1% higher than the stoichiometric ratio of lithium salt to (NH4)3PO4, for example, greater than about 2%, greater than about 3%, greater than about 4%, greater than about 5%, greater than about 7%, or about 10% higher than the stoichiometric ratio of lithium salt to (NH4)3PO4.

[0083] In any of steps 205, 210, 215, and 220, mixing may be performed. Additionally or alternatively, each of steps 205, 210, 215, and 220 may be performed at a temperature greater than or equal to about 18°C, greater than or equal to about 20°C, greater than or equal to about 25°C, greater than or equal to about 30°C, greater than or equal to about 60°C, greater than or equal to about 80°C, greater than or equal to about 90°C, greater than or equal to about 100°C, greater than or equal to about 120°C, or about 150°C; approximately 18°C ​​to about 150°C, approximately 18°C ​​to about 120°C, approximately 18°C ​​to about 90°C, approximately 18°C ​​to about 60°C, approximately 25°C to about 120°C, approximately 50°C to about 90°C, or approximately 80°C to about 120°C. Additionally or alternatively, each of steps 105, 110, and 115 may be performed for approximately 1 minute, approximately 5 minutes, approximately 10 minutes, approximately 15 minutes, approximately 30 minutes, approximately 60 minutes, approximately 2 hours, approximately 6 hours, approximately 12 hours, approximately 18 hours, approximately 24 hours, or approximately 48 hours; or approximately 1 minute to approximately 48 hours, approximately 1 minute to approximately 24 hours, approximately 1 minute to approximately 12 hours, or approximately 1 minute to approximately 6 hours. Approximately 1 minute to approximately 2 hours, approximately 5 minutes to approximately 48 hours, approximately 5 minutes to approximately 24 hours, approximately 10 minutes to approximately 48 hours, approximately 10 minutes to approximately 24 hours, approximately 10 minutes to approximately 12 hours, approximately 10 minutes to approximately 6 hours, approximately 10 minutes to approximately 2 hours, approximately 30 minutes to approximately 48 hours, approximately 30 minutes to approximately 24 hours, approximately 60 minutes to approximately 48 hours, approximately 60 minutes to approximately 24 hours, approximately 6 hours to approximately 24 hours, approximately 12 hours to approximately 24 hours, approximately 18 hours to approximately 24 hours, or approximately 24 hours to approximately 48 hours. For example, steps 205 and / or 210 may be performed at a temperature of approximately 18°C ​​to approximately 90°C for approximately 1 minute to approximately 2 hours, and steps 215 and / or 220 may be performed at a temperature of approximately 18°C ​​to approximately 60°C for approximately 10 minutes to approximately 2 hours.

[0084] Electroactive particles can be any electroactive material suitable for incorporation into an electrode. For example, electroactive particles can be suitable for the positive electrode. Such electroactive particles may include, but are not limited to, Li. (1+x) Mn₂O₄, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Coz )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, or a combination thereof. Additionally or alternatively, the electroactive particles may be suitable for a negative electrode. Such electroactive particles may include, but are not limited to, lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, or a combination thereof.

[0085] It is contemplated herein that the electroactive particles may have a circular geometry or an axial geometry. The term "axial geometry" refers to particles that generally have a rod-like, fibrous, or other cylindrical shape, which have a distinct long axis or longitudinal axis. Typically, the aspect ratio (AR) of a cylindrical shape (e.g., fiber or rod) is defined as AR = L / D, where L is the length of the longest axis and D is the diameter of the cylinder or fiber. Exemplary axially geometric electroactive material particles suitable for the present disclosure may have a high aspect ratio, for example, from about 10 to about 5,000. In certain variants, the first electroactive material particles having an axial geometry include fibers, wires, flakes, whiskers, filaments, tubes, rods, and the like.

[0086] The term "circular geometry" is generally used for particles with a low aspect ratio, such as close to 1 (e.g., less than 10). It should be noted that particle geometry may differ from a true circle and may include, for example, ellipsoids or ellipses, including oblate or flattened spheres, aggregated particles, polygonal (e.g., hexagonal) particles, or other shapes that typically have a low aspect ratio. An oblate spheroid may have a disk-like shape with a relatively high aspect ratio. Therefore, particles with a generally circular geometry are not limited to relatively low aspect ratios and spherical shapes.

[0087] Additionally or alternatively, the method may further include optional step 225, which includes applying a second slurry to a current collector, such as a positive or negative current collector. The second slurry may be applied by any suitable method or otherwise coated and cured by any suitable method to form an electrode layer comprising functional electrode particles. For example, as... Figure 2B As depicted herein, a second slurry may be applied or cast onto a third side 250 of the current collector 260. The first slurry can then be cured by any suitable method as described herein to form an electrode layer 270. The electrode layer 270 comprises electroactive particles 280 and Li3PO4 particles 290 dispersed within a polymer binder (not shown). Curing can be performed as described above, for example by drying and curing (e.g., heat curing, ultraviolet (UV) curing) to remove any solvents and / or water and to complete the crosslinking or polymerization reaction. Advantageously, the methods described herein prevent the segregation of smaller particles (e.g., Li3PO4) with larger particles (e.g., electroactive particles) to obtain functional electrode particles with a more uniform particle size distribution and no significant particle segregation.

[0088] II. Electrochemical Cells Lithium-ion electrochemical batteries typically include a negative electrode, a positive electrode, an electrolyte between the negative and positive electrodes for conducting lithium ions, and a porous membrane between the negative and positive electrodes to physically separate and electrically isolate the electrodes from each other while allowing free ion flow. When assembled in an electrochemical battery, such as a lithium-ion battery pack, the porous membrane is impregnated with a liquid electrolyte. It has been found that functional particles, such as those described herein, present, for example, in coatings on the porous membrane, as fillers in the porous membrane, and / or present in the electrode layers, can effectively remove trace amounts of water, hydrogen ions, hydrofluoric acid, and dissociated transition metal ions (e.g., Mn) from the liquid electrolyte. 2+ and Fe 2+ / 3+ The removal of lithium ions, polysulfides, and other target compounds from the liquid electrolyte does not inhibit lithium ion transport or net flow through the liquid electrolyte. Removing these target compounds from the liquid electrolyte during battery pack operation also helps prevent or mitigate degradation of various battery pack components, thereby improving battery pack life and cycle performance.

[0089] This document provides for use in battery packs, such as lithium-ion battery packs or electrochemical cells as capacitors. For example, exemplary and schematic illustrations of electrochemical cell 20 (also referred to as lithium-ion battery pack or battery pack 20) ​​are shown. Figure 3 The electrochemical cell 20 includes a negative electrode 22 (also referred to as a negative electrode layer 22), a first current collector 32 (also referred to as a negative electrode current collector 32) disposed at or near the negative electrode 22, a positive electrode 24 (also referred to as a positive electrode layer 24), a second current collector 34 (also referred to as a positive electrode current collector 34) disposed at or near the positive electrode 24, and a separator 26 disposed between the positive electrode layer 24 and the first current collector 32. The space between the negative electrode layer 22 and the positive electrode layer 24 (e.g., the separator 26) may be filled with an electrolyte 30. If pores exist in the negative electrode layer 22 and / or the positive electrode layer 24, the pores may also be filled with the electrolyte 30. The electrolyte 30 may impregnate, permeate, or wet the respective surfaces of the negative electrode layer 22, the positive electrode layer 24, and the porous separator 26 and fill the pores.

[0090] The first current collector 32 and the second current collector 34 respectively collect and transfer free electrons to and from the external circuit 40. The interruptible external circuit 40 and the load device 42 connect the first current collector 32 and the second current collector 34. The negative electrode layer 22, the positive electrode layer 24, and the separator 26 may each further contain an electrolyte 30 capable of transporting lithium ions. By being sandwiched between the negative electrode layer 22 and the positive electrode layer 24 to prevent physical contact and thus prevent short circuits, the separator 26 acts as both an electrical insulator and a mechanical carrier. In addition to providing a physical barrier between the electrodes 22 and 24, the separator 26 also provides a path of minimum resistance as an internal channel for lithium ions (and associated anions) to facilitate the operation of the battery pack 20. The separator 26 also contains an electrolyte solution in an open network during lithium-ion cycling to facilitate the operation of the battery pack 20.

[0091] When the negative electrode layer 22 contains a relatively large amount of intercalated lithium, the battery pack 20 can generate current during discharge through a reversible electrochemical reaction that occurs when the external circuit 40 is turned off (to connect the negative electrode layer 22 and the positive electrode layer 24). The chemical potential difference between the positive electrode layer 24 and the negative electrode layer 22 drives electrons generated at the negative electrode layer 22 by the oxidation of intercalated lithium to the positive electrode layer 24 via the external circuit 40. Lithium ions also generated at the negative electrode are simultaneously transported to the positive electrode layer 24 via the electrolyte 30 and the separator 26. Electrons flow through the external circuit 40 and lithium ions migrate through the separator 26 in the electrolyte 30 to form intercalated lithium at the positive electrode layer 24. The current through the external circuit 40 can be utilized and conducted through the load device 42 until the intercalated lithium in the negative electrode layer 22 is depleted and the capacity of the lithium-ion battery pack 20 decreases.

[0092] The lithium-ion battery pack 20 can be charged or recharged / re-energized at any time by connecting an external power source to it to reverse the electrochemical reactions that occur during battery discharge. Connecting an external power source to the lithium-ion battery pack 20 promotes the non-spontaneous oxidation of lithium intercalated in the positive electrode layer 24 to generate electrons and lithium ions. Electrons flowing back to the negative electrode layer 22 via the external circuit 40 and lithium ions carried back to the negative electrode layer 22 by the electrolyte 30 through the separator 26 recombine at the negative electrode layer 22, replenishing the intercalated lithium for consumption during the next battery discharge event. Thus, a complete discharge event followed by a complete charge event is considered a cycle in which lithium ions circulate between the positive electrode layer 24 and the negative electrode layer 22. The external power source that can be used to charge the lithium-ion battery pack 20 can vary depending on the size, construction, and specific end use of the lithium-ion battery pack 20. Some well-known and exemplary external power sources include, but are not limited to, AC wall sockets and vehicle alternators.

[0093] In many battery pack configurations, the negative electrode current collector 32, negative electrode layer 22, separator 26, positive electrode layer 24, and positive electrode current collector 34 are each prepared as relatively thin layers (e.g., a few micrometers or millimeters or less thick) and assembled as layers connected in an electrically parallel arrangement to provide a suitable energy pack. The negative electrode current collector 32 and the positive electrode current collector 34 collect and transfer free electrons to and from the external circuit 40, respectively.

[0094] In addition, the battery pack 20 may include various other components, though not depicted herein, that are known to those skilled in the art. For example, as a non-limiting example, the lithium-ion battery pack 20 may include a housing, gaskets, end caps, tabs, battery pack terminals, and any other conventional components or materials that may be located within the battery pack 20, including those located between or near the negative electrode layer 22, the positive electrode layer 24, and / or the separator 26. Figure 3 The battery pack 20 shown includes a liquid electrolyte 30 and illustrates a representative concept of battery pack operation.

[0095] As described above, the size and shape of the lithium-ion battery pack 20 can vary depending on the specific application it is designed for. Battery-powered vehicles and handheld consumer electronics are two examples, where the battery pack 20 is most likely designed with different sizes, capacities, and power output specifications. If required by the load device 42, the battery pack 20 can also be connected in series or parallel with other similar lithium-ion batteries or battery packs to produce greater voltage output and power density.

[0096] Accordingly, the battery pack 20 may generate an electric current to a load device 42 that can be operatively connected to the external circuit 40. The load device 42 may be fully or partially powered by the electric current passing through the external circuit 40 when the lithium-ion battery pack 20 is discharged. Although the load device 42 may be any number of known electric devices, several specific examples of power-consuming load devices include, as non-limiting instances, electric motors for hybrid or all-electric vehicles, laptop computers, tablet computers, mobile phones, and cordless electric tools or appliances. The load device 42 may also be a power generation device that charges the battery pack 20 for energy storage.

[0097] The present technology relates to improved electrochemical cells, in particular lithium-ion battery packs. In various scenarios, such batteries are used in vehicle or automotive transportation applications (e.g. motorcycles, boats, tractors, buses, motorcycles, recreational vehicles, campers, and tanks). However, the present technology may be used in a wide variety of other industries and applications, including, as non-limiting instances, aerospace components, consumer goods, devices, buildings (e.g. residences, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment or heavy machinery.

[0098] A. Positive Electrode Layer The positive electrode layer 24 may be formed of a first electroactive material that is capable of sufficiently undergoing lithium intercalation and deintercalation while acting as the positive terminal of the lithium-ion battery pack 20. It is contemplated herein that the first electroactive material may be in particulate form and may have a rounded geometry or an axial geometry as described herein. The positive electrode 24 may also include a polymeric binder material to structurally reinforce the lithium-based active material and the electrically conductive material. One exemplary common type of known material that may be used to form the positive electrode 24 is a layered lithium transition metal oxide. For example, in certain embodiments, the positive electrode layer 24 may comprise Li (1+x) Mn2O4, where 0.1 ≤ x ≤1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Nix Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤1, x + y + z +p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4 (M = Mn and / or Ni, 0 ≤ x ≤ 1); LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur (e.g., greater than 60% by weight based on the total weight of the cathode), or combinations thereof. Additionally or alternatively, the cathode layer 24 may include functional electrode particles as described herein, comprising a first electroactive material and Li3PO4.

[0099] Additionally or alternatively, the positive electrode layer 24 may optionally include a conductive material and / or a polymer binder as described herein. Examples of conductive materials include, but are not limited to, carbon black, graphite, acetylene black (such as KETCHEN), etc. TM Black or Denka TM The conductive materials include black carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), and combinations thereof. As used herein, the term "graphene nanosheet" refers to a nanosheet or stack of graphene layers. Such conductive materials in particle form can have circular or axial geometries as described above.

[0100] Examples of suitable polymeric adhesives include, but are not limited to, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), ethylene propylene diene monomer (EPDM) or carboxymethyl cellulose (CMC), nitrile butadiene rubber (NBR), styrene-butadiene rubber (SBR), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly(acrylate) PAA, polyimide, polyamide, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the polymeric adhesive may be a non-aqueous solvent-based polymer or an aqueous polymer. In particular, the polymeric adhesive may be a non-aqueous solvent-based polymer, which may exhibit lower capacity decay, provide a more robust mechanical network and improved mechanical properties to more effectively cope with silicon particle expansion, and have good chemical and heat resistance. For example, the polymeric adhesive may include polyimide, polyamide, polyacrylonitrile, polyacrylic acid, salts of polyacrylic acid (e.g., potassium, sodium, lithium), polyacrylamide, polyvinyl alcohol, carboxymethyl cellulose, or combinations thereof. The first electroactive material may be blended with a conductive material and / or at least one polymeric adhesive. For example, a first electroactive material and an optional conductive material can be slurried and cast together with such a binder and applied to the current collector. The polymer binder can play multiple roles in the electrode, including: (i) enabling electronic and ionic conductivity of the composite electrode, (ii) providing electrode integrity, such as the integrity of the electrode and its components, and its adhesion to the current collector, and (iii) participating in the formation of the solid electrolyte interface (SEI), which plays an important role since the kinetics of lithium intercalation depend primarily on the SEI.

[0101] In any embodiment, the first electroactive material may be present in the positive electrode in an amount greater than or equal to about 50% by weight, greater than or equal to about 60% by weight, greater than or equal to about 70% by weight, greater than or equal to about 80% by weight, greater than or equal to about 90% by weight, greater than or equal to about 95% by weight, or about 99% by weight; or about 50% by weight to about 99% by weight, about 70% by weight to about 99% by weight, or about 90% by weight to about 99% by weight.

[0102] Additionally or alternatively, the conductive material and the polymeric binder may each be present in the positive electrode in an amount of approximately 0.5% to approximately 20% by weight, approximately 1% to approximately 15% by weight, or approximately 1% to approximately 10% by weight, based on the total weight of the positive electrode.

[0103] B. Negative electrode layer The negative electrode layer 22 includes a second electroactive material as a lithium host material capable of serving as the negative terminal of a lithium-ion battery pack. The second electroactive material may comprise lithium (e.g., metallic lithium), lithium alloys, such as, but not limited to, lithium-silicon alloys, lithium-aluminum alloys, lithium-indium alloys, lithium-tin alloys, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, and combinations thereof, such as silicon mixed with graphite, and combinations thereof. Non-limiting examples of silicon-containing electroactive materials include silicon (amorphous or crystalline), or silicon-containing binary and ternary alloys, such as Si-Sn, SiSnFe, SiSnAl, SiFeCo, etc. In other variations, the negative electrode layer 22 may be a metal film or foil, such as a lithium metal film or a lithium-containing foil. The second electroactive material may be in particle form and may have the circular or axial geometry described above. Additionally or alternatively, the negative electrode layer 22 may include functional electrode particles as described herein, comprising a second electroactive material and Li3PO4.

[0104] Additionally, the negative electrode layer 22 may optionally include conductive materials as described herein and / or polymeric binders as described herein to improve the structural integrity of the electrode. For example, the second electroactive material and the electronically conductive or conductive material may be slurry-cast together with binders such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), ethylene propylene diene monomer (EPDM) or carboxymethyl cellulose (CMC), nitrile butadiene rubber (NBR), styrene-butadiene rubber (SBR), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly(acrylate) PAA, polyimide, polyamide, sodium alginate, or lithium alginate, and applied to the current collector. Examples of conductive materials include, but are not limited to, carbon black, graphite, acetylene black (such as KETCHEN), etc. TM Black or Denka TM (Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.) and combinations thereof.

[0105] In various respects, the second electroactive material may be present in the negative electrode in an amount of approximately 70% to approximately 99% by weight, approximately 80% to approximately 98% by weight, approximately 90% to approximately 99% by weight, or approximately 95% to approximately 98% by weight, based on the total weight of the negative electrode. Additionally or alternatively, the conductive material and the polymeric binder may each be independently present in the negative electrode in an amount of approximately 0.5% to approximately 15% by weight, approximately 1% to approximately 10% by weight, or approximately 1% to approximately 5% by weight, based on the total weight of the negative electrode.

[0106] C. Current collector The first current collector 32 and the second current collector 34 may each comprise a metal containing copper, aluminum, nickel, or an alloy thereof, stainless steel, or other suitable conductive material known to those skilled in the art. Additionally or alternatively, the first current collector 32 and the second current collector 34 may each be formed of or further comprise a carbon or carbon-metal (e.g., silver (Ag), aluminum (Al), zinc (Zn)) composite coating, for example having a thickness of approximately 500 nm to approximately 2 µm. In some aspects, the first current collector 32 and / or the second current collector 34 may be in the form of a foil, a slit mesh, and / or a braided mesh.

[0107] D. Porous membrane In any embodiment, the porous membrane 26 may comprise any organic or inorganic material that can physically and electrically isolate the positive and negative electrodes from each other while allowing lithium ions to flow freely between them. For example, the porous membrane 26 may comprise composite or nonwoven materials, such as sheets, meshes, or mats made of oriented or randomly oriented fibers, including but not limited to cotton, nylon, polyester, glass, and combinations thereof. As another example, the membrane 26 may comprise porous (e.g., microporous) polymeric materials, such as microporous polyolefin-based membranes or films. The porous membrane 26 may comprise a single polyolefin or a combination of polyolefins, such as polyethylene (PE), polypropylene (PP), polyamide (PA), poly(tetrafluoroethylene) (PTFE), polyvinylidene fluoride (PVdF), and / or poly(vinyl chloride) (PVC). The polyolefin may be a homopolymer (derived from a single monomer component) or a hybrid (derived from more than one monomer component), and may be linear or branched. If the hybrid polymer is derived from two monomer components, the polyolefin may exhibit any copolymer chain arrangement, including block copolymers or random copolymers. Similarly, if the polyolefin is a hybrid derived from more than two monomer components, it can also be a block copolymer or a random copolymer. In some embodiments, the porous membrane 26 may comprise a laminate of one or more polymer materials, such as a laminate of PE and PP. Commercially available polyolefin porous membrane substrates may include CELGARD, available from Celgard LLC. ® 2500 (single-layer polypropylene membrane) and CELGARD ® 2325 (Three-layer polypropylene / polyethylene / polypropylene membrane). Additionally or alternatively, the porous membrane 26 may include lithium-ion exchange zeolite particles as described herein, for example, as a filler.

[0108] In other aspects, the porous membrane 26 may be a fibrous membrane having a large number of pores extending between opposing surfaces and may have an average thickness of, for example, less than 1 mm. However, as another example, multiple discrete layers of similar or different polyolefins may be assembled to form the porous membrane 26. In addition to polyolefins, the porous membrane 26 may also contain other polymers, such as, but not limited to, polyethylene terephthalate (PET), polyvinylidene fluoride (PVdF), polyamides, polyimides, poly(amide-imide) copolymers, polyetherimides, and / or cellulose, or any other material suitable for establishing the desired porous structure. The polyolefin layers and any other optional polymer layers may be further included as fibrous layers in the porous membrane 26 to help provide the porous membrane 26 with suitable structural and porosity characteristics. The porous membrane 26 may have a thickness in the range of about 4 μm to about 25 μm.

[0109] Additionally or alternatively, the diaphragm 26 may include functional lithium-ion exchange zeolite particles as described herein as fillers within the diaphragm 26.

[0110] E. Coating In any embodiment, the porous membrane may include a coating comprising functional lithium-ion exchange zeolite particles as described herein. For example, such as Figure 4 As shown, in the battery pack 21, the porous separator 26 may have a first side 50 and an opposite second side 55. A coating 60 comprising functional lithium-ion exchange zeolite particles may be present on one or both sides 50, 55 of the separator 26. In some embodiments, such as Figure 4 As shown, the first side 50 and the second side 55 of the separator 26 may be coated with a coating 60. During assembly, the coating 60 present on the first side 50 faces and presses against the negative electrode layer 22, and the coating 60 present on the second side 55 faces and presses against the positive electrode layer 24. However, in some embodiments, the first side 50 of the separator 26 may be coated with the coating 60 and the second side 55 of the separator 26 may be uncoated, such that during assembly, the second side 55 of the separator 26 faces and presses against the positive electrode layer 24. In other embodiments, the second side 55 of the separator 26 may be coated with the coating 60 and the first side 50 of the separator 26 may be uncoated, such that during assembly, the first side 50 of the separator 26 faces and presses against the negative electrode layer 22. The coating 60 may additionally comprise a polymeric binder material as described herein.

[0111] The coating 60 may be formed continuously or discontinuously on the first and / or second sides 50, 55 of the diaphragm 26. For example, the coating 60 may be formed on the first side 50 of the diaphragm 26 such that the coating 60 covers the entire surface area or only a portion of the surface area of ​​the first side 50 of the diaphragm 26. Similarly, the coating 60 may be formed on the second side 55 of the diaphragm 26 such that the coating 60 covers the entire surface area or only a portion of the surface area of ​​the second side 55 of the diaphragm 26. The coating 60 may extend on the first and second sides 50, 55 of the diaphragm 26, and in some cases may partially extend into the micropores of the diaphragm 26.

[0112] In any embodiment, coating 60 may have a thickness of less than or equal to about 25 μm, less than or equal to about 20 μm, less than or equal to about 10 μm, less than or equal to about 5 μm, less than or equal to about 1 μm, or about 50 nm. Additionally or alternatively, coating 60 may have a thickness from about 50 nm to about 20 μm, from about 50 nm to about 10 μm, or from about 50 nm to about 5 μm. The thickness of coating 60 may be less than the thickness of diaphragm 26. For example, the thickness of coating 60 may be 50% or less of the thickness of diaphragm 26.

[0113] Functional particles, which serve as fillers in the negative electrode layer 22, positive electrode layer 24, coating 60, and / or as separator 26, can be located within the lithium-ion transport path through the electrochemical cells 20 and 21. During operation of the electrochemical cells 20 and 21, lithium ions can travel back and forth between the negative electrode 22 and positive electrode 24, and functional particles can be arranged such that lithium ions inevitably encounter one or more functional particles during this back-and-forth movement. Lithium ions can come into contact with functional particles, pass around functional particles, or pass through functional particles during their movement through the electrochemical cells 20 and 21. Functional particles can be formulated or selected to adsorb, remove, retain, or otherwise inhibit the movement of certain target compounds within the electrochemical cells 20 and 21 without adversely affecting the lithium-ion transport or net flow rate through the electrochemical cells 20 and 21. For example, functional lithium-ion exchange zeolite particles can be formulated or selected based on the aforementioned pore size, average particle size, and / or cation content to retain or suppress water molecules, polysulfide molecules, hydrogen ions, HF, and transition metal ions, such as Mn, within electrochemical cells 20 and 21. 2+ and Fe 2+ / 3+ Movement of ions. Target compounds can be physically and / or chemically trapped within functional particles.

[0114] Therefore, including functional particles in batteries 20 and 21 helps prevent a phenomenon known as “voltage droop,” reduces capacity decay and impedance, improves coulombic efficiency, helps maintain a uniform current distribution along the electrode / electrolyte interface, mitigates corrosion, and prevents gas evolution in batteries 20 and 21.

[0115] While not bound by theory, it is believed that functional particles could advantageously contribute to improving the cycle performance of electrochemical cells 20 and 21, for example, by trapping trace amounts of water, removing hydrofluoric acid (HF), and / or blocking polysulfide migration. Immobilizing trace water molecules within electrochemical cells 20 and 21 may help prevent the decomposition of the liquid electrolyte 30, and consequently, the decomposition of the lithium-based intercalation substrate material of the cathode 24. Hydrofluoric acid is highly corrosive and may be generated in electrochemical cells 20 and 21 during electrolyte decomposition, particularly through the reaction of LiPF6 with water according to the following reaction equation (2): LiPF6 + H2O ↔ LiF + POF3 + 2HF (2) The generated HF may increase the acidity of the liquid electrolyte 30, which could cause corrosion of the lithium-based intercalation host material of the positive electrode layer 24 and / or the current collectors 32, 34. Therefore, by acting as HF scavengers, the functional particles in the batteries 20, 21 may help mitigate the corrosion and degradation of various components of the batteries 20, 21.

[0116] Furthermore, it is believed that the functional particles in batteries 20 and 21 can trap transition metal ions, such as Mn 2+ and Fe 2+ / 3+ The presence of transition metal ions in the liquid electrolyte 30 may contribute to improved cycle life of the electrochemical cells 20 and 21, possibly due to the decomposition of the lithium-based intercalation host material in the positive electrode layer 24 and / or the presence of transition metal impurities in the positive electrode layer 24. Functional particles within the cells 20 and 21 may also contribute to improved robustness, for example, by improving the mechanical properties and thermal stability of the separator 26.

[0117] F. Electrolytes The positive electrode layer 24, the negative electrode layer 22, and the separator 26 may each include an electrolyte solution or system 30 within their pores, capable of conducting lithium ions between the negative electrode layer 22 and the positive electrode layer 24. Any suitable electrolyte 30 capable of conducting lithium ions between the negative electrode 22 and the positive electrode layer 24, whether in solid, liquid, or gel form, can be used in the lithium-ion battery packs 20 and 21. In some aspects, the electrolyte 30 may be a non-aqueous liquid electrolyte solution comprising a lithium salt dissolved in an organic solvent or a mixture of organic solvents. Many conventional non-aqueous liquid electrolyte solutions 30 can be used in the lithium-ion battery packs 20 and 21.

[0118] In some aspects, electrolyte 30 may be a non-aqueous liquid electrolyte solution comprising one or more lithium salts dissolved in an organic solvent or a mixture of organic solvents. For example, a non-limiting list of lithium salts soluble in organic solvents to form a non-aqueous liquid electrolyte solution includes lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalate)borate (LiB(C2O4)2) (LiBOB), and others. Lithium fluorooxalate borate (LiBF2(C2O4)), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethane)sulfonylimide (LiN(CF3SO2)2), lithium bis(fluorosulfonylimide) (LiN(FSO2)2) (LiSFI), lithium (triethylene glycol dimethyl ether)bis(trifluoromethanesulfonyl)imide (Li(G3)(TFSI)), lithium bis(trifluoromethanesulfonyl)amino (LiTFSA) and combinations thereof.

[0119] These and other similar lithium salts can be dissolved in a variety of non-aqueous, non-protic organic solvents, including but not limited to various alkyl carbonates such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), fluoroethylene carbonate (FEC)), linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC)), aliphatic carboxylic acid esters (e.g., methyl formate, methyl acetate, methyl propionate), γ-lactones (e.g., γ-butyrolactone, γ-valerolactone), chain ethers (e.g., 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane), and cyclic ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane). One or more salts may be present in the electrolyte at concentrations greater than or equal to about 1 M, greater than or equal to about 2 M, greater than or equal to about 3 M, or about 4 M, or about 1 M to about 4 M, about 1 M to 2 M, about 2 M to about 4 M, or about 3 M to about 4 M (number of moles of salt per liter of solvent).

[0120] Additionally or alternatively, the electrolyte may include additives that can, for example, improve the temperature and voltage stability of electrochemical battery materials (e.g., electrolyte 30, negative electrode layer 22, and positive electrode layer 24). Examples of suitable additives include, but are not limited to, ethylene carbonate, ethylene ethylene carbonate, propane sulfonate, and combinations thereof. Other additives may include diluents that do not coordinate with lithium ions but can reduce viscosity, such as bis(2,2,2-trifluoroethyl) ether (BTFE), and flame retardants, such as triethyl phosphate. Example

[0121] Example 1 Li3PO4 particles were synthesized by dissolving (NH4)3PO4 in distilled water at room temperature (25°C) in a container to prepare a 1 M solution. LiOH was then mixed into distilled water at room temperature (25°C) to prepare a 3 M solution. Equal volumes of both solutions were used, with (NH4)3PO4 gradually added to the LiOH solution to form Li3PO4, and LiOH gradually added to the (NH4)3PO4 solution to form Li3PO4. In each case, Li3PO4 powder precipitated at the bottom of the container. The mixture was centrifuged to remove excess water. The Li3PO4 powder was dried at 80°C for 8 hours and then calcined at 400°C for 4 hours. The dried Li3PO4 powder was collected for XRD and SEM analysis. Figure 5 The XRD patterns of Li3PO4 particles (510) formed by adding LiOH to (NH4)3PO4 and Li3PO4 particles (520) formed by adding (NH4)3PO4 to LiOH are shown. Figure 5 In the equation, the x-axis (530) corresponds to the 2θ value, and the y-axis (540) corresponds to the intensity. Figure 6A SEM images of Li3PO4 particles formed by adding LiOH to (NH4)3PO4 are shown to illustrate the formation of hollow spheres. Figure 6B This shows a SEM image of Li3PO4 particles formed by adding (NH4)3PO4 to LiOH.

[0122] The above description of the provided embodiments is for illustrative purposes only. It is not intended to be exhaustive or limiting of this disclosure. Elements or features of a particular embodiment are generally not limited to that particular embodiment, but are interchangeable and applicable to selected embodiments, if applicable, even if not explicitly shown or described. They can also be changed in many ways. Such changes should not be considered a departure from this disclosure, and all such modifications are intended to be included within the scope of this disclosure.

Claims

1. A method for preparing functional lithium-exchange zeolite particles for electrochemical batteries, the method comprising: (a) Combining a solution containing (NH4)3PO4 with lithium-ion exchange zeolite particles to form a first mixture; and (b) Adding a polymer binder and a lithium salt to a first mixture to form a first slurry containing functional lithium-ion exchange zeolite particles containing Li3PO4.

2. The method of claim 1, wherein the functional lithium-ion exchange zeolite particles comprise cages defined by 8-membered rings, 9-membered rings, 10-membered rings, 12-membered rings or combinations thereof, and wherein the cages contain Li3PO4.

3. The method of claim 1, wherein the functional lithium-ion exchange zeolite particles comprise zeolite materials having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof.

4. The method of claim 1, wherein the functional lithium-ion exchange zeolite particles comprise zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

5. The method of claim 1, wherein the lithium salt is selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, and combinations thereof.

6. The method of claim 1, wherein the concentrations of (NH4)3PO4 and lithium salt are each from 0.01 M to 1 M.

7. The method of claim 1, further comprising one or more of the following: (c1) Applying a first slurry to a first side, a second side, or both sides of a porous membrane, and curing the first slurry to form a coating comprising functional lithium-ion exchange zeolite particles, wherein the coating is present on the first side, the second side, or both sides of the porous membrane; and (c2) The first slurry is combined with the porous membrane and the first slurry is cured to form a filler containing functional lithium-ion exchange zeolite particles within the porous membrane.

8. A method for preparing functional electrode particles for electrochemical cells, the method comprising: (a) Combining a solution containing (NH4)3PO4 with a polymer binder to form a second mixture; (b) Add the electroactive particles to the second mixture; and (c) Adding a lithium salt to a second mixture to form a second slurry containing functional electrode particles, wherein the functional electrode particles comprise electroactive particles and Li3PO4.

9. The method of claim 8, wherein the lithium salt is selected from lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, and combinations thereof.

10. The method of claim 8, wherein the concentrations of (NH4)3PO4 and lithium salt are each from 0.01 M to 1 M.

11. The method of claim 8, wherein the electroactive particles comprise Li (1+x) Mn2O4, wherein 0.1 ≤ x ≤1; LiMn (2-x) Ni x O4, wherein 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, wherein 0 ≤ x ≤ 1, 0 ≤ y≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, wherein 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, wherein 0 < x < 0.3; LiNiCoAlO2; LiMPO4, wherein M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, wherein 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤1, x + y + z +p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, wherein M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, or a combination thereof.

12. The method of claim 8, further comprising: (d) Apply the second slurry to the third surface of the current collector; and (e) Curing the second slurry to form an electrode layer containing functional electrode particles.

13. An electrochemical battery comprising: A positive electrode layer containing a first electroactive material; A negative electrode layer spaced apart from the positive electrode, wherein the negative electrode contains a second electroactive material; A porous membrane disposed between the opposing surfaces of the negative electrode layer and the positive electrode layer; One or more liquid electrolytes that permeate the negative electrode layer, the positive electrode layer, and the porous membrane layer; and One or more of the following: (i) Functional lithium-ion exchange zeolite particles containing Li3PO4; and (ii) Functional electrode particles comprising (a) Li3PO4 and a first electroactive material, and / or (b) Li3PO4 and a second electroactive material.

14. The electrochemical battery of claim 13, wherein, when present, the functional lithium-ion exchange zeolite particles are present as one or more of the following: (i) A coating present on the first side, the second side, or both sides of a porous membrane; and (ii) Packing material in porous membranes.

15. The electrochemical battery of claim 13, wherein the functional lithium-ion exchange zeolite particles comprise cages defined by 8-membered rings, 9-membered rings, 10-membered rings, 12-membered rings or combinations thereof, and wherein the cages contain Li3PO4.

16. The electrochemical battery of claim 13, wherein the functional lithium-ion exchange zeolite particles comprise zeolite materials having a framework type selected from NAT, EDI, THO, ANA, YUG, GOO, MON, HEU, STI, BRE, FAU, MFI, LTL, LTA, and combinations thereof.

17. The electrochemical battery of claim 13, wherein the functional lithium-ion exchange zeolite particles comprise zeolite materials selected from zeolite A, zeolite Y, zeolite L, ZSM-5, and combinations thereof.

18. The electrochemical cell of claim 13, wherein, when present, the functional electrode particles are present in one or more of the following: (i) Positive electrode layer; and (ii) Second electrode layer.

19. The electrochemical cell of claim 13, wherein the first electroactive material is selected from Li (1+x) Mn2O4, wherein 0.1≤ x ≤ 1; LiMn (2-x) Ni x O4, wherein 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, wherein 0 ≤ x ≤1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, wherein 0<x<0.2, y<0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, wherein 0 < x < 0.3; LiNiCoAlO2; LiMPO4, wherein M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, wherein 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤1, 0 ≤ P ≤ 1, x + y + z +p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, wherein M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur and combinations thereof.

20. The electrochemical battery of claim 13, wherein the second electroactive material comprises lithium, lithium-silicon alloy, lithium-aluminum alloy, lithium-indium alloy, lithium-tin alloy, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, or a combination thereof.

Citation Information

Patent Citations

  • Separators for lithium-containing electrochemical cells and methods of making the same

    CN110071246A